The Importance of Physical and Mental Education for Children From an Islamic Education Perspective - Mariaty Podungge; Anugrah Lestari; Kasidi Kasidi (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The Problems of child molestation are still occurring and in some instances are victims. This provides anxiety for educators, especially parents who have children. The method used in this discussion is the library method (library research). The approach used is a qualitative approach with the analysis used being is descriptive analysis. The purpose of this study aims to describe the importance of physical and mental education for children from the perspective of Islamic education so that it can become a treasure of knowledge for educators so that children avoid bullying that occurs, especially in the school environment.The results showed that from an Islamic educational perspective, physical and mental education is very important for children. Physical education is a preventive measure to protect children's physique from bullying behavior and mental education is an effort to train children's ability to face the problems they experience. Physical education and mental education are needed for children according to their needs based on the observations of educators in their daily lives. This will be donewell if there is continuous communication between child educators in the home environment, namely parents and in the school environment, namely teachers.Keywords: Child; Physical, Education, Islam, Mental.